Unusual Presentation of Testicular Cancer with Tumor Thrombus Extending to the Inferior Vena Cava - Marie Dusaud; Younes Bayoud; François-Régis Desfemmes; Benoît Molimard; Xavier Durand (Case Reports in Urology)
A 45-year-old man with a left testis tumor with a 25 mm para-aortic lymph node swelling, multiple bilateral pulmonary metastases, bilateral pulmonary embolism, and inferior vena cava (IVC) thrombus underwent a radical orchidectomy in our institution. The thrombus extended from the left gonadal vein to the left renal vein to the IVC. The fluorine-18 fluorodeoxyglucose (f-FDG) positron emission tomography (PET) computerized tomography (CT) demonstrated a hypermetabolic focus in the retroperitoneum and in the IVC thrombus. Before orchidectomy only lactate dehydrogenase (LDH) was high but all the serum tumor markers increased postoperatively. The tumor was staged pT1N2M1aS1, which was an intermediate prognosis, based on the International Germ Cell Cancer Collaborative Group consensus (IGCCCG). After 4 courses of bleomycin, etoposide, and cisplatin (BEP) chemotherapy the patient’s tumor markers normalized and the thrombus disappeared. There was only one residual retroperitoneal lymph node M1. Retroperitoneal lymph node dissection was performed. The pathological examination revealed only necrotic tissues. The patient has been disease-free since surgery.